Evaluasi Program Tahfidz Al-Qur’an dengan Model CIPP di SMP Islam Bahrul Hikmah - Wirya Musyafiil Qulub; Nurlathifah Thulfitrah B (Jurnal Pendidikan Dirgantara, 2026)
This study aims to evaluate the Quran Tahfidz program at Bahrul Hikmah Islamic Junior High School using the Context, Input, Process, and Product (CIPP) evaluation model introduced by Stufflebeam. The findings of the research are as follows: First, the evaluation of the context aspect indicates that the program objectives have been comprehensively formulated. Data analysis confirms that the program implementation is well-aligned with the established goals, placing it in the 'good' category. Second, the evaluation of the input component reveals that the managerial competence of the administrators and the pedagogical capabilities of the educators have met the expected standards. Nevertheless, the infrastructure aspects require further optimization to foster a more conducive learning environment for students. Third, regarding the process aspect, the program implementation has generally achieved the targeted outcomes. However, observations identified obstacles predominantly stemming from students' internal factors; this implies the crucial role of teachers in integrating motivational stimuli as a preventive measure against declining learning enthusiasm. Fourth, the product evaluation shows that the daily memorization targets are generally achieved, although some students require remedial sessions. Ultimately, students are capable of completing the memorization of three juz within the three-year period.